A bargaining framework for the airline alliance revenue sharing problem. (2016) - Venkataraman, Sri Vanamalla; Ramachandran, Parthasarathy
The main objective of complementary code share flights is to increase scope of the partner's network. When complementary codeshared flights aim at maximising their combined revenue, it might lead to inequitable distribution of revenue. Through this work, we address this issue of achieving a fair division of the combined revenue generated by the alliance network. Information of an airline's valuation of their product is typically private and could be overstated to increase their share of revenue generated through codeshare agreements. We therefore develop a bargaining framework and derive the conditions under which a specific point in Core of the cooperative game can be achieved.